The Effect of Timeliness, Shipping Rates and Security of Goods on Customer Satisfaction of PT JNE in East Jakarta - Aswari, Nadira Wulan (Institut Transportasi dan Logistik Trisakti, 2024)
This study was conducted at PT JNE East Jakarta to examine the impact of timeliness (X1), shipping rates (X2), and security of goods (X3) on customer satisfaction (Y). The research sampled 130 customers using probability sampling techniques. Data were collected through observations, literature reviews, and questionnaires. Analytical methods included validity and reliability tests, classical assumption tests, and hypothesis testing using SPSS 26 software. The F-test results indicated a calculated F value of 137.742, exceeding the F table value, thus rejecting Ho and accepting Ha. This demonstrates that timeliness, shipping rates, and goods security significantly affect customer satisfaction at PT JNE East Jakarta. Furthermore, the R square value of 76.6% signifies that these factors contribute substantially to customer satisfaction, while the remaining 23.4% is influenced by other factors not covered in this study.